2013
DOI: 10.1038/srep01088
|View full text |Cite|
|
Sign up to set email alerts
|

Cell sorting in a Petri dish controlled by computer vision

Abstract: Fluorescence-activated cell sorting (FACS) applying flow cytometry to separate cells on a molecular basis is a widespread method. We demonstrate that both fluorescent and unlabeled live cells in a Petri dish observed with a microscope can be automatically recognized by computer vision and picked up by a computer-controlled micropipette. This method can be routinely applied as a FACS down to the single cell level with a very high selectivity. Sorting resolution, i.e., the minimum distance between two cells from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…The possible role of E-selectin in this static model of dPLB-985 binding to HUVECs is further supported by the inhibition of adhesion by soluble E-selectin. To assess the adhesion force between rMASP-1-treated HUVECs and dPLB-985 cells, we utilized the recently introduced computer controlled micropipette method [34,35]. Previously, it was applied to measure the adherence of macrophages and dendritic cells to fibrinogen, and to poly-L-Lys-graft-PEG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The possible role of E-selectin in this static model of dPLB-985 binding to HUVECs is further supported by the inhibition of adhesion by soluble E-selectin. To assess the adhesion force between rMASP-1-treated HUVECs and dPLB-985 cells, we utilized the recently introduced computer controlled micropipette method [34,35]. Previously, it was applied to measure the adherence of macrophages and dendritic cells to fibrinogen, and to poly-L-Lys-graft-PEG.…”
Section: Discussionmentioning
confidence: 99%
“…We used a computer controlled micropipette method to quantify the adhesion force between dPLB-985 cells and rMASP-1-treated HUVECs [34,35]. HUVECs were induced with 2 µM of rMASP-1, 300 nM thrombin for 6 hours, or 10 ng/mL TNFalpha for 24 hours or left untreated.…”
Section: Measurement Of Adhesion Between Dplb-985 Cells and Endothelimentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported that a micropipette controlled by computer vision allows automated single cell manipulations and sorting on a microscope. 24 A similar robot for the automated breeding of single cells has been recently developed. 25 This integrated instrument applies microwell arrays to immobilize cells on the surface for subsequent sorting.…”
mentioning
confidence: 99%
“…Efficiency of sorting after optimizing experimental parameters is not expected to strongly depend on cell size or shape. 32 We did not investigate cell viability in this study as we carried out exhaustive viability experiment in our previous report 24 using the same system without automated cell deposition. We argue that automated cell deposition is not expected to affect cell viability when using the same vacuum and pressure parameters as in case of the manual deposition.…”
mentioning
confidence: 99%